Lactobacillus acidophilus stimulates intestinal P-glycoprotein expression via a c-Fos/c-Jun-dependent mechanism in intestinal epithelial cells - Priyamvada, Shubha (Am J Physiol Gastrointest Liver Physiol, 2016)
Our previous studies showed that Lactobacillus acidophilus (LA) culture supernatant (CS) increased P-glycoprotein [Pgp/multidrug resistance 1 (MDR1)] function, expression, and promoter activity in Caco-2 cells. The current studies were designed to elucidate the molecular mechanisms mediating the stimulatory effects of LA CS on Pgp promoter activity. Deletion analysis indicated that the LA CS response element(s) is located in the −172/+428-bp region, and sequence analysis of this region revealed three potential binding sites for c-Fos or c-Jun: proximal activating protein (AP) 1a (−119/−98 bp), distal AP1b (−99/−78 bp), and AP1c (+175/+196 bp). LA CS (24 h) showed an approximately twofold increase in the protein expression of c-Fos and c-Jun in Caco-2 cells. Electrophoretic mobility shift assay showed that LA CS markedly increased the binding of Caco-2 nuclear proteins to AP1a and AP1b, but not AP1c. The DNA-protein complex was completely eliminated by c-Fos antibody, while c-Jun antibody partially eliminated the complex. Chromatin immunoprecipitation analysis also showed that LA CS enhanced the association of c-Fos and c-Jun (by ∼4- and 1.5-fold, respectively) with endogenous Pgp promoter in Caco-2 cells (p−172/+1). Interestingly, overexpression of c-Fos or c-Jun activated Pgp promoter by nearly twofold each. This increase was further enhanced (∼14-fold) when c-Fos and c-Jun were simultaneously overexpressed, suggesting that the presence of one of these transcription factors potentiates the effect of the other. These studies, for the first time, provide evidence for the involvement of c-Fos/c-Jun in stimulation of Pgp gene expression by LA CS in the human intestine.